Phosphorylation of serine96 of histidine-rich calcium-binding protein by the Fam20C kinase functions to prevent cardiac arrhythmia - Pollak, A. J.; Haghighi, K.; Kunduri, S.; Arvanitis, DA; Bidwell, P. A.; Liu, G. S.; Singh, V. P.; Gonzalez, D. J.; Sanoudou, D.; Wiley, S. E.; Dixon, J. E.; Kranias, EG (Proc Natl Acad Sci U S AProc Natl Acad Sci U S AProc Natl Acad Sci U S A, 2017)
Precise Ca cycling through the sarcoplasmic reticulum (SR), a Ca storage organelle, is critical for proper cardiac muscle function. This cycling initially involves SR release of Ca via the ryanodine receptor, which is regulated by its interacting proteins junctin and triadin. The sarco/endoplasmic reticulum Ca ATPase (SERCA) pump then refills SR Ca stores. Histidine-rich Ca-binding protein (HRC) resides in the lumen of the SR, where it contributes to the regulation of Ca cycling by protecting stressed or failing hearts. The common Ser96Ala human genetic variant of HRC strongly correlates with life-threatening ventricular arrhythmias in patients with idiopathic dilated cardiomyopathy. However, the underlying molecular pathways of this disease remain undefined. Here, we demonstrate that family with sequence similarity 20C (Fam20C), a recently characterized protein kinase in the secretory pathway, phosphorylates HRC on Ser96. HRC Ser96 phosphorylation was confirmed in cells and human hearts. Furthermore, a Ser96Asp HRC variant, which mimics constitutive phosphorylation of Ser96, diminished delayed aftercontractions in HRC null cardiac myocytes. This HRC phosphomimetic variant was also able to rescue the aftercontractions elicited by the Ser96Ala variant, demonstrating that phosphorylation of Ser96 is critical for the cardioprotective function of HRC. Phosphorylation of HRC on Ser96 regulated the interactions of HRC with both triadin and SERCA2a, suggesting a unique mechanism for regulation of SR Ca homeostasis. This demonstration of the role of Fam20C-dependent phosphorylation in heart disease will open new avenues for potential therapeutic approaches against arrhythmias.
Pollak, Adam JHaghighi, KobraKunduri, SwatiArvanitis, Demetrios ABidwell, Philip ALiu, Guan-ShengSingh, Vivek PGonzalez, David JSanoudou, DespinaWiley, Sandra EDixon, Jack EKranias, Evangelia GengT32 HL007444/HL/NHLBI NIH HHS/R01 DK018024/DK/NIDDK NIH HHS/R01 HL026057/HL/NHLBI NIH HHS/T32 HL125204/HL/NHLBI NIH HHS/F32 HL136122/HL/NHLBI NIH HHS/R01 HL064018/HL/NHLBI NIH HHS/R01 DK018849/DK/NIDDK NIH HHS/Research Support, N.I.H., ExtramuralResearch Support, Non-U.S. Gov't2017/08/09 06:00Proc Natl Acad Sci U S A. 2017 Aug 22;114(34):9098-9103. doi: 10.1073/pnas.1706441114. Epub 2017 Aug 7.
Keywords: Amino Acid Sequence; Animals; Arrhythmias, Cardiac/genetics/*metabolism/prevention & control; Calcium-Binding Proteins/genetics/*metabolism; Casein Kinase I/genetics/*metabolism; Cell Line, Tumor; Cells, Cultured; Extracellular Matrix Proteins/genetics/*metabolism; Humans; Mice, Knockout; Mice, Transgenic; Mutation; Myocytes, Cardiac/metabolism; Phosphorylation; Rats; Sarcoplasmic Reticulum Calcium-Transporting ATPases/genetics/metabolism; Sarcoplasmic Reticulum/metabolism; Serine/genetics/metabolism